Identification of UX dimensions for incident reporting systems with mobile applications in urban contexts: a longitudinal study. Issue 4 (November 2016) - Winckler, Marco; Bernhaupt, Regina; Bach, Cédric
Abstract Incident reporting systems enable end-users to report problems that they have experienced in their working activities to authorities. Such applications are sought to sense the quality of the environment, thus enabling authorities to promote safety and well-being among citizens. Many governments are now promoting the use of mobile applications allowing citizens to report incidents in their neighbourhood to the administration. Nonetheless, it is not clear which user experience dimensions affect the adoption of incident reporting systems, and to what extent anticipated use of the system (anticipated UX) is a determinant for predicting the user experience with the final application. In order to understand how citizens perceive incident reporting systems and which factors affect the user experience (UX), we have performed empirical studies including interviews in early phases of the development process and empirical user testing of advanced prototypes. In this paper, we present the results of a longitudinal study on the evolution of the perception of UX dimensions along the development process, from interviews to running prototypes. Hereafter, we describe the method that has been used for coding the findings of these empirical studies according to six UX dimensions (includingvisual and aesthetic experience, emotions, stimulation, identification, meaning & value andsocial relatedness/co -experience ). Moreover, we describe how the findings have been associated with users' tasks. The findings from interviews and user testing indicate that whilst the perceived importance of some UX dimensions (such asidentification andmeaning & value ) remains similar over time, other dimensions such asstimulation andemotions do evolve. Beyond the practical implications of this study for the design of incident reporting systems, this work presents an approach that allows comparing the results of UX assessments in different phases of the process.